Meta‐Analysis of Genomewide Association Studies Reveals Genetic Variants for Hip Bone Geometry. (19th March 2019) - Hsu, Yi‐Hsiang; Estrada, Karol; Evangelou, Evangelos; Ackert‐Bicknell, Cheryl; Akesson, Kristina; Beck, Thomas; Brown, Suzanne J; Capellini, Terence; Carbone, Laura; Cauley, Jane; Cheung, Ching‐Lung; Cummings, Steven R; et al.
ABSTRACT: Hip geometry is an important predictor of fracture. We performed a meta‐analysis of GWAS studies in adults to identify genetic variants that are associated with proximal femur geometry phenotypes. We analyzed four phenotypes: (i) femoral neck length; (ii) neck‐shaft angle; (iii) femoral neck width, and (iv) femoral neck section modulus, estimated from DXA scans using algorithms of hip structure analysis. In the Discovery stage, 10 cohort studies were included in the fixed‐effect meta‐analysis, with up to 18, 719 men and women ages 16 to 93 years. Association analyses were performed with ∼2.5 million polymorphisms under an additive model adjusted for age, body mass index, and height. Replication analyses of meta‐GWAS significant loci (at adjusted genomewide significance [GWS], threshold p ≤ 2.6 × 10 –8 ) were performed in seven additional cohorts in silico. We looked up SNPs associated in our analysis, for association with height, bone mineral density (BMD), and fracture. In meta‐analysis (combined Discovery and Replication stages), GWS associations were found at 5p15 ( IRX1 and ADAMTS16) ; 5q35 near FGFR4 ; at 12p11 (in CCDC91 ); 11q13 (near LRP5 and PPP6R3 (rs7102273)). Several hip geometry signals overlapped with BMD, including LRP5 (chr. 11). Chr. 11 SNP rs7102273 was associated with any‐type fracture ( p = 7.5 × 10 –5 ). We used bone transcriptome data and discovered several significant eQTLs, including rs7102273 and PPP6R3 expression ( p = 0.0007), and rs6556301 (intergenic, chr.5 near FGFR4 ) and PDLIM7 expression ( p = 0.005). In conclusion, we found associations between several genes and hip geometry measures that explained 12% to 22% of heritability at different sites. The results provide a defined set of genes related to biological pathways relevant to BMD and etiology of bone fragility. © 2019 American Society for Bone and Mineral Research.